Children’s Education in The Story of Single Mothers in Qur’ȃn - Moh. Toriqul Chaer; Alef Theria Wasim; Akif Khilmiyah (International Journal of Education and Learning, 2019)
This research aims to find the concept of child education in the story of the single true mother in the Qur'an. The study uses library studies with subjective hermeneutic approaches. The results of the study were found: first, the current status of single mother hakiki and single mother majazi. Second, the relevance of children's education in the story of single mothers follows the stage of the psychology of child development. It is starting from the prenatal phase, covering the child's spiritual and physical education. In the postnatal period, it includes education, supervision and responsible children. Child education in a single mother is done holistically, not partially and not mechanically